Dual-mode T1 and T2 magnetic resonance imaging contrast agent based on ultrasmall mixed gadolinium-dysprosium oxide nanoparticles: synthesis, characterization, and in vivo application. (17th August 2015) - Tegafaw, Tirusew; Xu, Wenlong; Ahmad, Md Wasi; Baeck, Jong Su; Chang, Yongmin; Bae, Ji Eun; Chae, Kwon Seok; Kim, Tae Jeong; Lee, Gang Ho
Abstract: A new type of dual-mode T 1 and T 2 magnetic resonance imaging (MRI) contrast agent based on mixed lanthanide oxide nanoparticles was synthesized. Gd 3+ ( 8 S7/2 ) plays an important role in T 1 MRI contrast agents because of its large electron spin magnetic moment resulting from its seven unpaired 4f-electrons, and Dy 3+ ( 6 H15/2 ) has the potential to be used in T 2 MRI contrast agents because of its very large total electron magnetic moment: among lanthanide oxide nanoparticles, Dy2 O3 nanoparticles have the largest magnetic moments at room temperature. Using these properties of Gd 3+ and Dy 3+ and their oxide nanoparticles, ultrasmall mixed gadolinium-dysprosium oxide (GDO) nanoparticles were synthesized and their potential to act as a dual-mode T 1 and T 2 MRI contrast agent was investigated in vitro and in vivo . The D-glucuronic acid coated GDO nanoparticles ( d avg = 1.0 nm) showed large r 1 and r 2 values ( r 2 / r 1 ≈ 6.6) and as a result clear dose-dependent contrast enhancements in R 1 and R 2 map images. Finally, the dual-mode imaging capability of the nanoparticles was confirmed by obtaining in vivo T 1 and T 2 MR images.